BEBERAPA SIFAT SMALL RIEMANN SUMS FUNGSI TERINTEGRAL HENSTOCK-KURZWEIL DARI RUANG EUCLIDïƒ‚n KE RUANG BANACH X - Khabibah, Siti; Darmawijaya, Soeparna (MATEMATIKA, 2011)
In this paper we discussed some properties of Henstock-Kurzweil integrable functions from the Euclidean Spaces Ã‚ninto Banach space , Locally Small Riemann Sums dan Globally Small Riemann Sums. Â